Surveillance and follow-up examinations in cutaneous melanoma - Garbe, Claus; Schadendorf, Dirk (Onkologie, 2003)
The main goal of follow-up examinations of patients with cutaneous melanomas is early diagnosis of developing recurrent or second tumors. Timely recognition of recurrence has a relevant effect on the prognosis. In 80% of the cases recurrences are diagnosed for the first time in the course of follow-up when follow-up procedures are carried out systematically. Most recurrences are discovered during a physical examination. Sonographic examination of the lymph nodes is also a very sensitive method which can lead to the diagnosis of locoregional recurrences before they are palpable. Further image-producing techniques are not necessary for surveillance of primary tumors. In contrast to former recommendations, new research indicates that less extensive diagnostic procedures are sufficient in primary tumor stages, especially when the tumor thickness of the melanoma is less than 1 mm. Consequently, costs can be reduced considerably without additional risk to the patient.